Culture-Based Risk Management (Experimental Study on Saving and Loan Cooperative in Badung Regency) - Suartana, I Wayan; Jati, I Ketut (Journal of A Sustainable Global South; Vol 1 No 1 (2017): February 2017DO - 10.24843/jsgs.2017.v01.i01.p04, 2020)
This  research  aims  to provide  an  overview  of the  application  of risk management  based  on  local  cultural  values conducted  by Saving and Loan Cooperative  (SLC) in Badung Regency  as the main component  in the implementation  of good corporate  governance  by optimising  the local  cultural  values  such as Tri Hita  Karana  and  Catur  Purusha  Artha.   By putting forward  the  local  cultural  values,  the  Saving  and  Loan  Cooperative   (SLC)  is  expected   to  grow  and  flourish  with  the internalisation of strong cultural values leading to good and appropriate corporate  governance.  This research  is conducted by an experimental  study using questionnaire  as the media. The research  sample is the Saving and Loan Cooperative's employees  in Badung  Regency.  The results  confirm  our hypothesis  with  a total  of 56  respondents.  The total  number  of respondents  are 56 (fifty-six)  people.   The  test  results  show  that  Tri  Hita Karana  and  Catur  Purusha  Artha  individually  strengthen  the  risk management of Saving and Loans Cooperative. Keywords:   Risk Management,  Saving and Loan Cooperative,  Tri Hita Karana, Catur Purusha Artha